ANALISIS PENGARUH SIZE PERUSAHAAN DAN IOS TERHADAP PRAKTIK EARNING MANAGEMENT PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI - Wirmie Eka Putra; Rita Friyani; Delta Ferryandi Wibowo (Jurnal Manajemen Terapan dan Keuangan, 2012)
This study aims to obtain empirical evidence about the impact of firm size and IOS on the practice of earning management. Objects in this study were 11 mining companies listed on the Stock Exchange along the period of 2006-2010. Earning management was calculated with the modified Jones models, while IOS measured by market to book value of equity, and size was measured by logarithm of total assets. This study use panel data regression models with Eviews 7.1 includes a series of test models, such as the Chow test and the Hausman test to choose the best model among the Common Effect, Fixed Effect and Random Effect. These results indicate that the firm size significantly influence the practice of earning management inversely. Large firms are having less earning management practise, and vice versa. Meanwhile, no significant effect was found between the IOS and earning management.